Nonionic surfactant enhanced biodegradation of m-xylene by mixed bacteria and its application in biotrickling filter. (3rd October 2018) - Wang, Liping; Xu, Ruiwei; Yang, Bairen; Wei, Shaohua; Yin, Ningning; Cao, Chun
ABSTRACT: In this study, m -xylene biodegradation was examined in bacteria-water mixed solution and biotrickling filter (BTF) systems amended with the nonionic surfactant Tween 80. The mixed bacteria were obtained from the activated sludge of a coking plant through a multisubstrate acclimatization process. High-throughput sequencing analysis revealed that Rhodanobacter sp. was the dominant species among the mixed bacteria. In the bacteria-water mixed solution, the bacterial density increased with increasing Tween 80 concentration. Hence, Tween 80 could be utilized as substrate by the mixed bacteria. Tween 80, with concentrations of 50–100 mg L −1, could enhance the bioavailability of m -xylene and consequently improve the degradation efficiency of m -xylene. However, further increasing the initial concentration of Tween 80 would decrease the degradation efficiency of m -xylene. At concentrations exceeding 100 mg L −1, Tween 80 was preferentially degraded by the mixed bacteria over m -xylene. In BTF systems, when the m -xylene inlet concentration was 1200 mg m −3 and the empty bed residence time was 20 sec, the removal efficiency and elimination capacity of BTF1 with Tween 80 addition were at most 20% and 24% higher than those of BTF2 without Tween 80 addition. Overall, the integrated application of the mixed bacteria and surfactant was demonstrated to be a highly effective strategy for m -xylene waste gas treatment. Implications : The integrated application of mixed bacteria and surfactant was demonstrated to be a promising approach for the highly efficient removal of m -xylene. Surfactant can activate mixed bacteria to degrade m -xylene by increasing its bioavailability. Besides, surfactant can be utilized as carbon source by the mixed bacteria so that the growth of mixed bacteria can be promoted. It is expected that the integrated application of both technologies will become more common in future chemical industry.